Highly Efficient Removal of Methylene Blue Dye from Wastewater Using CaO-MnFe2O4 Nanoparticles Prepared with Teak Leaf Extract - Rodiah, Siti; Ramadhani, Ericha (al Kimiya: Jurnal Ilmu Kimia dan Terapan, 2023)
This research aimed to synthesize a semiconductor photocatalyst CaO-MnFe2O4 nanoparticles using teak (Tectona grandis) leaf extract to degrade methylene blue in wastewater. Nanocatalysts were prepared through the precipitation method, while anthocyanins in extract acted as a reducing and stabilizing agent in this process. The presence of spinel ferrite (Fe-O), and manganese ferrite were indicated by using a Fourier transform infrared (FTIR) spectrometer that showed vibrational peaks at areas 538 cm-1 and 872 cm-1, respectively. The crystalline phase of CaO-MnFe2O4 was confirmed using an X-Ray diffractometer (XRD) that appeared peaks at 2θ: 18º; 29º; 34º; 47º; 52º, while peaks at 2θ: 32º; 37º and 54º indicated CaO. Through the Debye-Scherrer equation, the CaO-MnFe2O4 nanoparticles had an average crystal size of 8.6 nm. The morphology of CaO-MnFe2O4 nanoparticles was clearly visible in the Scanning electron microscope (SEM) results in the form of fibrous clumps. The CaO-MnFe2O4 nanoparticles could degrade methylene blue with a degradation percentage of 86% over 240 min.